Tribocorrosão de revestimentos soldados de Stellite sobre aço inoxidável austenítico aplicados em homogeneizadores da indústria alimentícia - Rodrigues, Thales Marcelo Pereira (2024)
In industrial processes, it is necessary to ensure the reliability of assets. In the tomato processing sector, during the last harvest seasons, several shutdowns occurred due to wear, compromising the economic gains of the sector. For tomato processing industries, the homogenizer is a critical piece of equipment that operates under compression. In this condition, a piston, sliding through a sleeve, forces the paste to pass through an orifice to break the macromolecules and bring the fibers closer together. When wear occurs, the reduction of the section causes the system to depressurize, leading to a loss of function. In addition to wear, corrosion may occur due to the composition of the tomato extract. By understanding the wear and corrosion that occur in this system, the application of a more resistant alloy coating is evaluated. Therefore, by characterizing the wear mechanisms that occur in practice, a Stellite alloy can be applied to the homogenizer piston through welding to make it more resistant. Thus, the general objective of this work is to evaluate the applicability of Stellite alloy coatings applied by welding in homogenizers. Using a band saw, samples were taken from the worn region of the cylinder. Subsequently, ultrasonic cleaning was performed, and the samples were analyzed under a microscope. Grooves, likely related to abrasive wear, were identified, as well as plastic deformation and delamination. At the end of this stage, it was possible to understand the morphology of the wear marks and their origin. To define the welding parameters used in the deposition of the Stellite coatings, six beads were applied based on the supplier's operating range. In this process, bead number 5 showed the best performance for the coating application. After the coating was applied to the test specimens, they were subjected to tribocorrosion wear tests. Then, a morphological analysis of the wear was performed (SEM, EDS, Profilometry). In the tribocorrosion test, it was found that Stellite did not acquire better resistance compared to AISI 316L, as, in the presence of chlorides, the cobalt alloy becomes more susceptible to corrosion, making the wear more severe, especially in the passive region.